2021
DOI: 10.1186/s12885-021-07868-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment center volume on outcomes in gastroenteropancreatic neuroendocrine tumor patients

Abstract: Background Medical centers with varying levels of expertise treat gastroenteropancreatic neuroendocrine tumors (GEP-NETs), which are relatively rare tumors. This study assesses the impact of center volume on GEP-NET treatment outcomes. Methods We used the Surveillance, Epidemiology, and End Results (SEER) registry linked to Medicare claims data. The data includes patients diagnosed between 1995 and 2010 who had no health maintenance organization (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…We may suppose that patients unseen by the CoE have a less severe NEN disease; indeed, in the epidemiologic data, primaries from the rectum/appendix/stomach, known to often be localized and low grade, are more common ( 15 ). In our study, the pancreas and small intestine primaries represented the majority of the cohort, as was the case in other expert centre and/or high volume centres ( 12 , 16 ). Further efforts are necessary to increase systematic presentation of NEN patients at a RENATEN MDT.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…We may suppose that patients unseen by the CoE have a less severe NEN disease; indeed, in the epidemiologic data, primaries from the rectum/appendix/stomach, known to often be localized and low grade, are more common ( 15 ). In our study, the pancreas and small intestine primaries represented the majority of the cohort, as was the case in other expert centre and/or high volume centres ( 12 , 16 ). Further efforts are necessary to increase systematic presentation of NEN patients at a RENATEN MDT.…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, many studies linked better survival to early involvement of a specialized team for sarcoma management ( 11 , 15 , 21 , 22 , 23 ). Regarding NEN, only one recent retrospective study indicated a link between centre volume and patient’s survival ( 16 ). More studies have, on the other hand, examined the impact of a specialized NEN MDT, leading to significant changes in patients’ management for 21–51% of those studied ( 12 , 13 ); interestingly, Zandee and coworkers reported fewer changes after specialized MDT for gastroduodenal, appendiceal and rectal NET ( 13 ), which in the present study were managed less often in the CoE.…”
Section: Discussionmentioning
confidence: 99%
“…66 A recent analysis of the SEER-Medicare database found that most patients with GEP-NENs receive surgery at medium or high-volume centers. 67 However, they also found no significant difference in the racial composition of those treated across hospital volumes. Unfortunately, this study included a relatively small sample size of patients with mixed surgically and medically treated patients research funding for early-stage investigators and trainees from under-represented groups.…”
Section: Discussionmentioning
confidence: 92%
“…Recognizing that our cohort has limitations in the assessment of cost-scaling, we reviewed a broader landscape (SEER database) to assess the US potential healt hcare impact. SEER18 reported an annual incidence of 2518 NETs 11 of which ∼77% underwent surgery 30 . In this group, ∼66% have localized or “completely” resectable disease; we projected ∼1280 R0 surgical resections annually 11 .…”
Section: Discussionmentioning
confidence: 97%